2007
DOI: 10.1038/sj.bjc.6603557
|View full text |Cite
|
Sign up to set email alerts
|

A physical analysis of the Y chromosome shows no additional deletions, other than Gr/Gr, associated with testicular germ cell tumour

Abstract: Testicular germ cell tumour (TGCT) is the most common malignancy in men aged 15 -45 years. A small deletion on the Y chromosome known as 'gr/gr' was shown to be associated with a two-fold increased risk of TGCT, increasing to three-fold in cases with a family history of TGCT. Additional deletions of the Y chromosome, known as AZFa, AZFb and AZFc, are described in patients with infertility; however, complete deletions of these regions have not been identified in TGCT patients. We screened the Y chromosome in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 29 publications
2
19
0
Order By: Relevance
“…Indeed, 25% of GCC susceptibility could be attributed to genetic factors according to an elegant epidemiological study by Czene and coworkers [129]. In targeted studies specific genomic risk loci/Single Nucleotide Polymorphisms (SNPs) were identified at the Y chromosome (gr/gr microdeletion) [130,131] and in the FSH [132]/androgen receptors [133]. Risk loci were also found in PTEN [134] and loci related to genes involved in steroid hormone metabolism [135,136], cAMP signaling [137], insulin like growth factor signaling [138], DNA damage response [139,140], estrogen metabolism/signaling [141][142][143], gonadotropin regulation [144], TP53-KITL interaction [145], sex determination [146] and prostate/colorectal/breast cancer (8q24 locus) [147].…”
Section: Genetic Risk Factorsmentioning
confidence: 99%
“…Indeed, 25% of GCC susceptibility could be attributed to genetic factors according to an elegant epidemiological study by Czene and coworkers [129]. In targeted studies specific genomic risk loci/Single Nucleotide Polymorphisms (SNPs) were identified at the Y chromosome (gr/gr microdeletion) [130,131] and in the FSH [132]/androgen receptors [133]. Risk loci were also found in PTEN [134] and loci related to genes involved in steroid hormone metabolism [135,136], cAMP signaling [137], insulin like growth factor signaling [138], DNA damage response [139,140], estrogen metabolism/signaling [141][142][143], gonadotropin regulation [144], TP53-KITL interaction [145], sex determination [146] and prostate/colorectal/breast cancer (8q24 locus) [147].…”
Section: Genetic Risk Factorsmentioning
confidence: 99%
“…The variable penetrance of the tumor phenotype in Ter mice of different genetic backgrounds faithfully mimics the etiology of germ cell tumors in humans. Germ cell tumors are the most common form of cancer in men between the ages of 15 and 34, and are highly correlated with ethnicity and other complex genetic influences (Brown et al, 1987; Brown et al, 1986; Hussain et al, 2008; Linger et al, 2007). …”
Section: Introductionmentioning
confidence: 99%
“…Based on the comparison between three genetic backgrounds, we suggest that mitotic arrest is a threshold effect influenced by the levels of multiple factors that vary between strains, including positive and negative regulators of the cell cycle and possibly miRNAs. The variability that we see among genetic backgrounds reflects the etiology of the human disease, where the incidence of germ cell tumors is correlated with ethnicity and other complex genetic factors that have not been completely explained (Brown et al, 1987; Brown et al, 1986;Hussain et al, 2008;Linger et al, 2007;Looijenga, 2009;Oosterhuis and Looijenga, 2005).…”
Section: Cip1mentioning
confidence: 99%